Polyomavirus nephropathy and Cytomegalovirus nephritis in renal allograft recipients - Agrawal Vinita; Gupta Ramesh; Jain Manoj; Prasad Narayan; Sharma Raj (Wolters Kluwer Medknow Publications, 2010)
Background: Polyomavirus nephropathy (PVN) and Cytomegalovirus (CMV) disease are the most common viral pathogens causing allograft dysfunction in renal allograft recipients. They have been observed in transplant recipients with increasing frequency in the recent years with various reports describing wide differences in the incidence of these infections in renal allografts. We present our experience with Polyomavirus (PV) infection and CMV infection in allograft of renal transplant recipients from a transplant centre in North India performing more than 100 transplants per year. Materials and Methods: 390 renal allograft specimens from 327 patients over a 4 year period, presenting with renal dysfunction were re-evaluated for presence of PVN and CMV disease utilizing histo-morphological features and immunohistochemistry. Results: Thirteen patients with PVN and four with CMV disease were identified. All patients were on triple drug immunosuppression receiving cyclosporine, prednisolone and tacrolimus or MMF. The mean period of diagnosis of viral infection after transplant was 12.4 months (seven days to 3.5 yrs) for PVN and 4.8 months (two to seven months) for CMV nephritis. Biopsies showed varying degrees of tubulointerstitial inflammation, viral inclusions and evidence of tubular damage. Associated features of acute rejection were present in 69.2% of patients with PVN. Conclusion: Histological features of PVN involving the kidneys have considerable morphological overlap with acute rejection while CMV disease presents primarily as tubulointerstitial inflammation. We observed a prevalence of 4% for PVN and 1.2% for CMV nephritis in renal allografts.